Mechanisms and efficacy of disinfection in ceramic water filters: A critical review - Venis, R. A.; Basu, O. D. (Critical reviews in environmental science and technology, 2021)
Diarrheal illnesses claim the lives of hundreds of thousands of children each year, most of whom live in rural and low-income communities. Ceramic Water Filters (CWF) are widely regarded as one water treatment technology with the potential to increase access to safe drinking water. While physical filtration mechanisms are a key contributor to improving the water safety, silver is commonly added to improve disinfection performance. Therefore, a thorough review of silver disinfection efficacy and disinfection mechanisms in relation to CWFs are critically important. This paper reviews filter mechanisms and efficacy for bacteria removal for cases with and without silver addition. Method of silver application (dipping, painting, or co-firing) is assessed. Silver release and retention is discussed. The findings from this paper illustrate that eluted silver contributes to filter bacterial disinfection. However, more research is needed on the impact of silver on preventing a "slime layer" on the filter surface and receptacle. Silver application method, water quality and particle characteristics were demonstrated to impact release. For instance, co-firing results in the most consistent elution over time but at lower concentrations than other methods. Finally, research into alternative metals to silver for enhanced disinfection present emerging opportunities within the CWF field.